Data on cardiac defects, morbidity and mortality in patients affected by RASopathies. CARNET study results - Giulio Calcagni; Giuseppe Limongelli; Angelo D'Ambrosio; Francesco Gesualdo; Maria Cristina Digilio; Anwar Baban; Sonia B. Albanese; Paolo Versacci; Enrica De Luca; Giovanni B. Ferrero; Giuseppina Baldassarre; Gabriella Agnoletti; et al. (Data in Brief, 2018)
A comprehensive description of morbidity and mortality in patients affected by mutations in genes encoding for signal transducers of the RAS-MAPK cascade (RASopathies) was performed in our study recently published in the International Journal of Cardiology. Seven European cardiac centres participating to the CArdiac Rasopathy NETwork (CARNET), collaborated in this multicentric, observational, retrospective data analysis and collection. In this study, clinical records of 371 patients with confirmed molecular diagnosis of RASopathy were reviewed. Cardiac defects, crude mortality, survival rate of patients with 1) hypertrophic cardiomyopathy (HCM) and age <2 years or young adults; 2) individuals with Noonan syndrome and pulmonary stenosis carrying PTPN11 mutations; 3) biventricular obstruction and PTPN11 mutations; 4) Costello syndrome or cardiofaciocutaneous syndrome were analysed. Mortality was described as crude mortality, cumulative survival and restricted estimated mean survival. In particular, with this Data In Brief (DIB) paper, the authors aim to report specific statistic highlights of the multivariable regression analysis that was used to assess the impact of mutated genes on number of interventions and overall prognosis.